Effect of Occupational Safety and Health on Employee Work Productivity at PT. Kelompok Empat Puluh - Veronica; Silvia Yunata; Vincent; Melinda Siregar (Jurnal Mantik, 2022)
Occupational health and safety are elements that can affect work productivity. This study aims to determine and analyze the effect of occupational safety and health on the work productivity of PT. Kelompok Empat Puluh. This type of research is explanatory research. Researchers took the population in this study as many as 40 people who work at the company. The sampling technique that will be used is to use a saturated sample where the entire population will be used as a research sample so that as many as 40 research samples are obtained. In this research, the distribution of questionnaires will be measured using a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous test and partial test. The results showed that either partially or simultaneously, occupational health and safety had a positive and significant effect on the sales of PT. Kelompok Empat Puluh. Based on the results of this study, the implications for management are to improve health and safety at work.